PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 001 PASIR KELAMPAIAN KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU - Suryamaini Suryamaini; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was caused by the low students’ learning outoomes,with an average grade at least 55.while the criteria completeness (KKM) is 65. Among students numbering 27 students, who reached KKM only 4 students with thevclassical completeness of 14,8 %.this research is a classroom action research (PTK) that is condicted to improove students’ learning outcomes IPS at fourth grade of SDN 001 Pasir Kelampaian by using cooperative learning type script. Formulation of the problems : is the implementation of cooperative learning type script can improve students’ learning outcomes at fourth grade of SDN 001 Pasir Kelampaian. This study was conducted from march, 20 th until april, 11 th consisting 2 cycles. The subjects were students at fourth grade of SDN 001 Pasir Kelampaian consisting 26 students who used the data source. On this thisis, data colletin is in the form of syllabus, lesson plan (RPP), and students worksheet (LKS) . this thesis presents the results obtained from the value of learning daily tests brfore action by an average 55 increasedin the first cycle with an average 64. The second cycle increased by an average 70. Activities became a teacher in learning process at the fisst cycle the fisst meeting 71% at 83% the second meeting and the second meeting to 96%. Data activity of studendt at the first cycle at the first meeting 71% and 79% at the second meeting. While at the first meeting of the second cycle 83% at the second meeting to 96%. Results of the study at fourth grade of SDN 001 Pasir Kelampaian that implementation of cooperative learning type script can improve students’ learning outcomes IPS at fourth grade of SDN 001 Pasir Kelampaian.Keywords : cooperative learning type script, learning outcomes.